2016
DOI: 10.1155/2016/6389347
|View full text |Cite
|
Sign up to set email alerts
|

Radiopacity of Methacrylate and Silorane Composite Resins Using a Digital Radiographic System

Abstract: The aim of this study was to evaluate the radiopacity of silorane and methacrylate resin composites, comparing them to the enamel, dentin, and aluminum penetrometer using a digital image. From six resin composites (Filtek™ P90, Filtek Z350, Filtek Z350 XT flow, Tetric Ceram, TPH Spectrum, and SureFil SDR flow) cylindrical disks (5 × 1 mm) were made and radiographed by a digital method, together with a 15-step aluminum step-wedge and a 1 mm slice of human tooth. The degree of radiopacity of each image was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
2
5
1
Order By: Relevance
“…This may be explained by the lower concentration and not the type of the radiopacifying agent, which has similar atomic number with the other radiopacifying agents used. This is in agreement with Firoozmand et al who also reported low radiopacity values for Filtek P90 (silorane‐based composite) but slight higher from enamel's radiopacity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be explained by the lower concentration and not the type of the radiopacifying agent, which has similar atomic number with the other radiopacifying agents used. This is in agreement with Firoozmand et al who also reported low radiopacity values for Filtek P90 (silorane‐based composite) but slight higher from enamel's radiopacity.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the highest radiopacity values presented Te‐Econom Plus, Tetric Ceram, and Tetric EvoCeram, which contain ytterbium (Yb) as a radiopacifying agent. This evidence coincides with the results of previous studies . Ytterbium has the highest atomic number (Z = 70) of the radiopacifying agents used in the tested composite materials providing higher radiopacity in lower concentrations compared to the other radiopacifying agents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…found that enamel and dentin has radiopacity of 0.91 mm and 0.63 equivalent of Al, respectively. [ 42 ] Hrab et al . compared radiopacity of TotalFill BC sealer with hydroxyapatite with zinc (5%–10%), hydroxyapatite with silver (10%–15%), aluminosilicate glasses (45%–50%), zirconium oxide (10%–15%), and calcium hydroxide (5%–10%) and found that TotalFill had Radiopaque of average 4 ± 0.15 (unit) which was greater radiopacity than experimental materials.…”
Section: Premixed Bioceramics As a Pulp Capping Agentsmentioning
confidence: 99%
“…The diversity of chemical composition and proportions, which typically are not detailed by manufacturers, has been mainly associated with a wide-ranging scale of radiopacity values observed in the scientific literature [ 14 ]. However, the choice of imaging system and exposure parameters was also reported to exert an influence on the radiopacity level [ 15 ], leading to intra-material variations up to 25% [ 16 ] and thus raising difficulties in making a conclusive evaluation and comparison of the published data. Moreover, the radiopacity of HCSCs is routinely assessed after the complete setting of the material in time periods of 24 h to 28 days, whereas the clinically radiographic images are obtained immediately after the endodontic treatment is finished.…”
Section: Introductionmentioning
confidence: 99%